REFERENCE ERROR IN BOOK MANUSCRIPT FROM LIPI: HOW GOOD OUR SCIENTISTS ARE IN COMPOSING REFERENCES - Helmiawan, Martinus (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2020)
Reference lists from 13 book manuscripts that were submitted to LIPI Press in 2018 written by the writersfrom LIPI were examined. In total, there were 879 reference list entries, and the accuracy of each citationwas examined. The examination was conducted by firstly determining the type of error and referencestyle used for cross-checking. Afterwards, each entry was thoroughly checked for errors. Found errorswere grouped into each type of error. The result, only 100 entries were error-free, and from the 779entries that contain errors, 3,651 errors were found. The errors were categorized into 1,576 punctuationerrors; 396 capitalization errors; 338 italicization errors, 206 spelling and word choice errors; 126 syntaxerrors; 642 spacing errors; 46 extraneous information errors; and 321 missing data errors. From thatresult, error rate of 4.15 was achieved. This paper concluded that the overall huge error rate found showsthe negligence of the writers in composing references.